Factors Affecting the Periapical Status of Root-Filled Canals: A Cross-Sectional Study at the Undergraduate Level - George Moreira Costa; Suelleng Maria Santos Soares; Paula Cristina Pelli Paiva; Flaviana Dornela Verli; Patrícia Furtado Gonçalves; Sangela Maria da Silva Pereira; Rudys Rodolfo De Jesus Tavarez; Janir Alves Soares; Etevaldo Matos Maia Filho (Hindawi Limited, 2017)
Objective. The aim was to evaluate the influence of multiple factors on the periapical status of endodontically treated (ET) teeth. Methods. The patients were clinically and radiographically reevaluated after root canal therapy. The quality of the root-filled canals, coronal restorations, intraradicular posts, dental caries, and periodontal parameters were associated with the teeth's periapical status. Results. The 122 patients provided 154 ET teeth; 97.4% teeth were asymptomatic, and 75.5% had a normal periapical status. The percentage of perfect, satisfactory, and deficient root-filled canals was of the order of 41.6%, 46.1%, and 12.3%, respectively. The percentage of adequate and inadequate coronal restorations was 31.2% and 68.8%, respectively. A total of 14.9% teeth had intraradicular posts, and 29.2% had cavitated carious lesions in the dentin. Gingival bleeding was observed in 31.8% of teeth, and dental biofilm was visible in 58.4%. A total of 11.7% showed pathologic tooth mobility, and 22.1% teeth were diagnosed with periodontal disease. Conclusions. Carious lesions, gingival bleeding, and tooth mobility were significantly associated with the occurrence of periapical lesions in root-filled canals.